1988
DOI: 10.1159/000125070
|View full text |Cite
|
Sign up to set email alerts
|

Loperamide, an Opiate Analog, Differently Modifies the Adrenocorticotropin Responses to Corticotropin-Releasing Hormone and Lysine Vasopressin in Patients with Addison’s Disease

Abstract: Loperamide is a peripheral opiate agonist able to inhibit ACTH secretion. In this work, the interactions between loperamide and two ACTH secretagogues, lysine vasopressin (LVP) and corticotropin-releasing hormone (CRH), were investigated in patients with Addison’s disease. After loperamide (16 mg orally) or placebo administration, 5 patients received LVP (0.06 IU/kg i.v. over 1 h) and 6 patients received oCRH (1 µg/kg i.v. as bolus). In all patients loperamide induced a significant fall in plasma ACTH levels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Merritt et al [3] have reported about a suppressive effect of loperamide on a calmodulin-dependent phosphodiesterase which was significant between 10"6 and 10"4 M. Both modes of action have been shown to exist in the gastrointesitnal system. While the antidiar rheal activity of loperamide can be inhibited by naloxone [4], loperamide's antisecretoiy action in the colon is caused by a block of the calmodulin system [5], Recently, loperamide was reported to suppress ACTH and cortisol levels in normal subjects and in patients with Addison's disease [6][7][8]. Loperamide also modified the adrenocorticotropin responses to corticotropin-releasing hormone (CRH) and to lysine vasopressin [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Merritt et al [3] have reported about a suppressive effect of loperamide on a calmodulin-dependent phosphodiesterase which was significant between 10"6 and 10"4 M. Both modes of action have been shown to exist in the gastrointesitnal system. While the antidiar rheal activity of loperamide can be inhibited by naloxone [4], loperamide's antisecretoiy action in the colon is caused by a block of the calmodulin system [5], Recently, loperamide was reported to suppress ACTH and cortisol levels in normal subjects and in patients with Addison's disease [6][7][8]. Loperamide also modified the adrenocorticotropin responses to corticotropin-releasing hormone (CRH) and to lysine vasopressin [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…While the antidiar rheal activity of loperamide can be inhibited by naloxone [4], loperamide's antisecretoiy action in the colon is caused by a block of the calmodulin system [5], Recently, loperamide was reported to suppress ACTH and cortisol levels in normal subjects and in patients with Addison's disease [6][7][8]. Loperamide also modified the adrenocorticotropin responses to corticotropin-releasing hormone (CRH) and to lysine vasopressin [7,8]. The sup pressive effect of loperamide on ACTH secretion was shown to be reversed by naloxone [6].…”
Section: Introductionmentioning
confidence: 99%